2020
DOI: 10.1111/gbb.12679
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking paternal expression of imprinted Grb10 are risk‐takers

Abstract: The imprinted genes Grb10 and Nesp influence impulsive behavior on a delay discounting task in an opposite manner. A recently developed theory suggests that this pattern of behavior may be representative of predicted effects of imprinted genes on tolerance to risk. Here we examine whether mice lacking paternal expression of Grb10 show abnormal behavior across a number of measures indicative of risk‐taking. Although Grb10+/p mice show no difference from wild type (WT) littermates in their willingness to explore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
12
1
Order By: Relevance
“…Unexpectedly, no significant difference in hypothalamus Grb10 gene expression was detected between the groups ( t = 1.586, P =0.135) ( Figure 2 A). This was surprising since it had been reported that paternal expression of imprinted Grb10 directly regulates risk-taking behavior in the PORT task [ 19 ], so we extended our profiling to other imprinted genes. In contrast, Igf2 levels were significantly increased in PatMS offspring ( t = 4.381, P <0.001) ( Figure 2 B), consistent with a previous finding in a model of paternal generalized daily stress [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Unexpectedly, no significant difference in hypothalamus Grb10 gene expression was detected between the groups ( t = 1.586, P =0.135) ( Figure 2 A). This was surprising since it had been reported that paternal expression of imprinted Grb10 directly regulates risk-taking behavior in the PORT task [ 19 ], so we extended our profiling to other imprinted genes. In contrast, Igf2 levels were significantly increased in PatMS offspring ( t = 4.381, P <0.001) ( Figure 2 B), consistent with a previous finding in a model of paternal generalized daily stress [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PORT protocol was adapted from Dent et al, 2020 [ 19 ] and represented in Figure 1 A. Two to four mice per litter from four control and four PatMS litters were trained for PORT.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously found that the Prader-Willi syndrome imprinted gene, Magel2, significantly affects foraging modules ( Hörndli et al, 2019 ), building on studies by others showing that Magel2 affects anxiety-like responses, feeding, activity, and 5-HT signaling ( Kozlov et al, 2007 ; Mercer et al, 2009 ). Moreover, Grb10 impacts impulsive choice and risk-taking behaviors ( Dent et al, 2016 , 2018 , 2020 ). Grb10 is a canonical imprinted gene that resides next to Ddc, and it is paternally expressed in the mouse and human brain and maternally expressed in the body ( Arnaud et al, 2003 ; Menheniott et al, 2008 ; Sanz et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%